Strategy for Norways Pension Fund Global - Goetzmann, William N., (SAGE Knowledge. Cases., 2017)
The September 2013 electoral victory of a center-right coalition after eight years of Socialist rule promised to bring changes to Norway, including to the countrys vaunted sovereign wealth fund. Erna Solberg, the leader of Norway's Conservative Party and the countrys new prime minister, had promised to review the funds structure and policies. During the election campaign, she noted that the investments "might be too big to be handled by just one fund." She added, "You could split it either on getting different handlers to compete better, or have different objectives for your investments in different funds. Were going to explore it, develop and see if its a good idea."